Engineered cell therapies for autoimmune diseases: evaluating CAR-T and CAR-M progress and prospects - Zheng, Mingxuan; Chen, Jiale; Yang, Hong (Frontiers in Immunology, 2025)
Autoimmune diseases (AID) comprise a diverse group of disorders driven by aberrant B-cell and T-cell reactivity against self-tissues. In recent years, cell-based therapies utilizing engineered T cells have emerged as a promising therapeutic strategy for AIDs. Notably, chimeric antigen receptor (CAR)-T cells have demonstrated the ability to selectively target and eliminate autoreactive immune populations, including pathogenic B cells and antibody-producing plasma cells. Beyond T-cell modulation, macrophages (MΦs) exhibit remarkable plasticity, differentiating into pro-inflammatory (M1) or anti-inflammatory (M2) phenotypes in response to microenvironmental cues. Advances in genetic engineering have enabled the development of CAR-MΦs (CAR-M), which hold potential for adoptive immunotherapy in certain diseases. However, CAR-M therapy remains experimental and requires further clinical validation. This review systematically evaluates the therapeutic potential of CAR-T and CAR-M in AIDs, comparing their respective advantages and limitations to provide a comprehensive foundation for future translational applications.